Leadership Influence Toward Professionalism in Teaching and Learning Quality at IAIN Raden Intan Bandar Lampung - Siti Patimah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
This research was conducted at IAIN Raden Intan Bandar Lampung which is aimed at revealing the influence of leadership on the lecturers’ professionalism and teaching-learning quality. The study uses a quantitative approach through descriptive correlation technique and regression by using parametric statistical analysis. The research findings show that the three hypothesis can be accepted as supported by empirical as following: 1) the influence of leadership upon lecturers’ professionalism is 12.5%, with the strength low correlation as (0.354); 2) the leadership influence toward the learning quality is 0.81% with a low correlation strength i.e. 0.285; and 3) the lecturers’ professionalism influence on learning quality is equal to 63.9%, with a strong correlation (0.799).